Discourse Analysis of Trilateral Partnership - Bhattarai, Gaurav (KMC Research Journal, 2017)
This article analyzes the proposed idea of trilateral partnership between India, China and Nepal as a discourse. Available documents on proposed trilateral partnership, speeches and statements delivered by government key leaders, newspaper reports, public opinions and views related to the idea of trilateralism have been analyzed for this discourse. This article sheds light on the India’s response to the trilateral partnership floated by Nepal and China’s response to the same.